The Dynamics of Conflict, Asymmetric Access, and Governance Transparency in Bima’s Annual Public Land Leasing Policy - Daaris, Yuli Yanti (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to critically examine the tensions embedded within stakeholder relations in the implementation of the annual leasing policy of former collateral land previously held by village officials in Bima Regency—an initiative intended to optimize Local Own-Source Revenue (PAD), yet one that has instead given rise to complex social, political, and ecological ramifications. Employing a qualitative case study approach and in-depth interviews with key actors including government officials, local residents, auction participants, and community leaders this research reveals that the policy’s execution is fraught with non-transparent practices, conflicts of interest, and structural inequities in access to resources. Findings indicate that the land auction process is frequently marred by suspicions of winner manipulation, where the highest bids are overlooked, thereby exacerbating economic disparities and eroding public trust in local governance. Paradoxically, although the policy was conceived to enhance agricultural access for the underprivileged, empirical evidence suggests that economically dominant groups disproportionately reap its benefits. Furthermore, the short-term leasing model incentivizes unsustainable land use, contributing to soil degradation and undermining long-term local food security. This study underscores the critical need for policy reformulation grounded in principles of distributive justice, the strengthening of oversight mechanisms, and the inclusive engagement of communities in policy design and evaluation processes. Ultimately, the study not only highlights the urgency of establishing equitable and accountable public land governance but also offers a theoretical reflection on how localized resource conflicts mirror broader power asymmetries in Indonesia’s public policy landscape.